STRATEGI GURU DALAM MENILAI KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN IBADAH: STUDI FENOMENOLOGI - Anas, Moh.; Sugeng (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
This study aims to describe teacher strategies in assessing students' religious character through worship practices at Syaichona Cholil Junior High School in Samarinda. The study used a qualitative approach with a phenomenological design, involving Islamic Religious Education teachers, homeroom teachers, and students as subjects. Data were collected through interviews and observations, then analyzed using the Miles and Huberman model. The results revealed that religious character assessment was conducted through observational strategies (observing daily behavior), reflective strategies (encouraging introspection), and collaborative strategies (involving spiritual mentors). Worship practices such as Dhuha prayer, tadarus (religious recitation), and communal prayer served as the primary and effective assessment tools for internalizing religious values. The main supporting factors were a strong school religious culture and teachers' commitment as role models, despite obstacles such as subjectivity in assessment and limited observation time. This study concluded that the integration of diverse assessment strategies, consistent worship practices, and school environmental support are key to successfully shaping students' holistic religious character